TITLE: TRANSLANGUAGING AS A SCAFFOLDING STRATEGY IN MULTILEVEL EFL CLASSROOMS IN UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
Meeting the varied demands of students with different levels of English proficiency is a problem for teachers in Uzbekistan's increasingly multilingual EFL classes. In order to promote language development in multilevel classrooms, this research investigates translanguaging as an engaging and inclusive scaffolding technique. Based on sociocultural theory and translanguaging pedagogy, I consider effective teaching methods and student reactions from my own experience working with ninth-grade Uzbek students getting ready for CEFR-based tests and IELTS examinations.